NHPI- and TBAI-Co-Catalyzed Synthesis of Allylic Esters from Toluene Derivatives and Alkenes - Li, Chengliang; Deng, Hongmei; Jin, Tao; Li, Chunju; Jia, Xueshun; Li, Jian (Synlett, 2018)
An N-hydroxyphthalimide (NHPI) and tetrabutylammonium iodide (TBAI) co-catalyzed oxidative coupling reaction of toluene derivatives and alkenes has been disclosed. This method can serve as a new strategy to access allylic ester using toluene derivatives as oxyacylating reagent. This metal-free protocol also features the readily available starting materials, broad substrate scope, and mild reaction conditions.
Keywords: oxyacylation; toluene derivatives; oxidative coupling; allylic ester; metal-free